The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1073/pnas.0701248104
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochic acid and the etiology of endemic (Balkan) nephropathy

Abstract: Endemic (Balkan) nephropathy (EN),environmental mutagen ͉ p53 mutation ͉ urothelial cancer ͉ DNA adduct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
592
0
13

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 528 publications
(639 citation statements)
references
References 35 publications
(56 reference statements)
27
592
0
13
Order By: Relevance
“…This group published a series of papers showing that aristolochic acid is the main risk factor and causative agent of BEN. 17,18 In the last few decades, exposure to this environmental nephrotoxin has decreased due to significant improvements in farming and milling practices. However, further studies are needed to explain why, in a region with a uniform way of farming, the prevalence of BEN remains stable in one village, and while in another it decreases, as presented here.…”
Section: Discussionmentioning
confidence: 99%
“…This group published a series of papers showing that aristolochic acid is the main risk factor and causative agent of BEN. 17,18 In the last few decades, exposure to this environmental nephrotoxin has decreased due to significant improvements in farming and milling practices. However, further studies are needed to explain why, in a region with a uniform way of farming, the prevalence of BEN remains stable in one village, and while in another it decreases, as presented here.…”
Section: Discussionmentioning
confidence: 99%
“…with upper urothelial cancer exclusively affecting farming villagers [1,2,3]. Based on our results, EN is considered to be an environmental form of aristolochic acid nephropathy (AAN) [1,2.3].…”
Section: Endemic (Balkan) Nephropathy (En) Is a Chronic Tubulointerstmentioning
confidence: 99%
“…Gluhovschi et al reported that although therapeutic remedies based on AA products are used in the EN affected area, no relationship between these remedies and the development of EN or of tumors was observed [8]. However, they used HPLC for detection of AA in plasma, which is less sensitive than the mass spectrometry we recently used [1,2]. In addition, when re-analyzing their data, it does appear that AA was used more frequently in the endemic area.…”
mentioning
confidence: 95%
“…Alternative approaches such as high resolution melting still require a conventional sequencing step and also lack sensitivity. Although the microarray based p53 Amplichip (Roche), improves on sensitivity with a detection limit as low as 2% 31 , it is limited in the type of mutation that it can detect.…”
Section: Introductionmentioning
confidence: 99%